2x+8x=2(x+1)+5(8x+6)

Simple and best practice solution for 2x+8x=2(x+1)+5(8x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+8x=2(x+1)+5(8x+6) equation:


Simplifying
2x + 8x = 2(x + 1) + 5(8x + 6)

Combine like terms: 2x + 8x = 10x
10x = 2(x + 1) + 5(8x + 6)

Reorder the terms:
10x = 2(1 + x) + 5(8x + 6)
10x = (1 * 2 + x * 2) + 5(8x + 6)
10x = (2 + 2x) + 5(8x + 6)

Reorder the terms:
10x = 2 + 2x + 5(6 + 8x)
10x = 2 + 2x + (6 * 5 + 8x * 5)
10x = 2 + 2x + (30 + 40x)

Reorder the terms:
10x = 2 + 30 + 2x + 40x

Combine like terms: 2 + 30 = 32
10x = 32 + 2x + 40x

Combine like terms: 2x + 40x = 42x
10x = 32 + 42x

Solving
10x = 32 + 42x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42x' to each side of the equation.
10x + -42x = 32 + 42x + -42x

Combine like terms: 10x + -42x = -32x
-32x = 32 + 42x + -42x

Combine like terms: 42x + -42x = 0
-32x = 32 + 0
-32x = 32

Divide each side by '-32'.
x = -1

Simplifying
x = -1

See similar equations:

| 12x+23=5x+205 | | 4(2+n)=-2(n+4)+4 | | 161-4x=23x+23 | | 4(2+n)=-2(n+4 )+4 | | 7-8x=22-15x | | 4(2+n)=-2(1+5n) | | -155-8x=9x+15 | | 2+10x=92+x | | 4(2+n)=-2(1+5x) | | 2x+11=-9-8x | | x+[x(.08)+x(.20)]=1280 | | 0=x^2-4x-7 | | -25-5x=7-9x | | 3c^2-8c+5=0 | | -2x-2=11 | | 8(a-7)=6(1+8a)+6a | | 5x-2=13x-98 | | -2(1-3r)+5=3(4+3r) | | 4.85=0.05(p)+1.85 | | 3x+34=12x-74 | | -7(2-2a)=-2(-4a+7) | | y=0.05(28)+1.85 | | 6(p+8)=-4(2p-5) | | 81b^2-100=0 | | -[6x-(4x+8)]=9+(6x+3) | | -(p+2)=2(p-7) | | 88-42=2.66(h-7) | | p-42=2.66(20-7) | | x+4=28 | | p-42=2.66(18-7) | | p-42=2.66(7-7) | | 5.5x-64=3.5+14 |

Equations solver categories